Performance Evaluation of Multi-carrier PWM Techniques: PD, POD and APOD - Mustafa INCI (International Journal of Applied Methods in Electronics and Computers, 2019)
In industrial applications, modulation strategies play a significant role to provide the effective voltage generation at the outputs of inverter structures. Also, the modulation strategies are important to generate output voltages with lower harmonic distortions. For this purpose, there are several modulation techniques to produce stepped voltage waveforms by reducing harmonics for high voltage levels. Therefore, this work introduces the comparative study of multi-carrier based pulse width modulation (PWM) methods used in high power rated inverters. In this regard, phase disposition (PD), phase opposition disposition (POD) and alternative phase opposition disposition (APOD) PWM strategies are tested in five-level cascaded H-bridge inverter. The performance consequences are received for different carrier frequencies, and total harmonic distortions are evaluated for tested methods. The results show that total harmonic distortion in APOD-PWM controlled inverter is less than other methods. In addition, total harmonic distortion values are performed for frequency values, which are from 0.5 kHz to 4 kHz.